Stromal myofibroblasts in focal reactive overgrowths of the gingiva - Leonardo Silveira Damasceno; Fernanda da Silva Gonçalves; Edson Costa e Silva; Elton Gonçalves Zenóbio; Paulo Eduardo Alencar Souza; Martinho Campolina Rebello Horta (Sociedade Brasileira de Pesquisa Odontológica, 2012)
Focal reactive overgrowths are among the most common oral mucosal lesions. The gingiva is a significant site affected by these lesions, when triggered by chronic inflammation in response to microorganisms in dental plaque. Myofibroblasts are differentiated fibroblasts that actively participate in diseases characterized by tissue fibrosis. The objective of this study was to evaluate the presence of stromal myofibroblasts in the main focal reactive overgrowths of the gingiva: focal fibrous hyperplasia (FFH), peripheral ossifying fibroma (POF), pyogenic granuloma (PG), and peripheral giant cell granuloma (PGCG). A total of 10 FFHs, 10 POFs, 10 PGs, and 10 PGCGs from archival specimens were evaluated. Samples of gingival mucosa were used as negative controls for stromal myofibroblasts. Oral squamous cell carcinoma samples, in which stromal myofibroblasts have been previously detected, were used as positive controls. Myofibroblasts were identified by immunohistochemical detection of alpha smooth muscle actin (α-sma). Myofibroblast immunostaining was qualitatively classified as negative, scanty, or dense. Differences in the presence of myofibroblasts among FFH, POF, PG, and PGCG were analyzed using the Kruskal-Wallis test. Stromal myofibroblasts were not detected in FFH, POF, PG, or PGCG. Consequently, no differences were observed in the presence of myofibroblasts among FFH, POF, PG, or PGCG (p > 0.05). In conclusion, stromal myofibroblasts were not detected in the focal reactive overgrowths of the gingiva that were evaluated, suggesting that these cells do not play a significant role in their pathogenesis.